A new method for histamine release from purified peripheral blood basophils using monoclonal antibody-coated magnetic beads - Nishi, Hiroshi; Nishimura, Shinji; Higashiura, Masahito; Ikeya, Norie; Ohta, Hideki; Tsuji, Tetsuo; Nishimura, Masaji; Ohnishi, Shigeo; Higashi, Hideo (Journal of immunological methods, 2000)
A new method for evaluating histamine release from purified basophils was developed. Basophil-containing leukocytes were directly purified from a small amount of peripheral blood using monoclonal antibody BA312-coated magnetic beads. The purified basophils still rosetted to magnetic beads maintained a normal response to anti-IgE and to dust mite allergen in comparison with the conventional method using washed leukocytes. This methodology facilitates the purification of basophils, anti-IgE- and allergen-induced histamine release, and subsequent histamine determination within only 3 h. The released histamine was analyzed by an enzyme-linked immunosorbent assay (ELISA) with a characteristic detection profile. Since all steps were performed in 96-well microplates, many clinical samples could be analyzed at the same time, permitting easy applications in routine laboratories.